Myricitrin - a flavonoid isolated from the Indian olive tree (Elaeocarpus floribundus) - inhibits Monoamine oxidase in the brain and elevates striatal dopamine levels: therapeutic implications against Parkinson's disease. - Banerjee, C.; Nandy, S.; Chakraborty, J.; Kumar, D. (Food & function, 2022)
Flavonoids exhibit several biological activities including inhibition of Monoamine oxidase (MAO), an enzyme that metabolizes several neurotransmitters. Thus, MAO inhibitors are well included in traditional therapeutic practices to fine-tune neuromotor behavior. This study aims to isolate flavonoids from a less explored plant of northeast India, named Indian olive (Elaeocarpus floribundus; Ef, family Elaeocarpaceae), and evaluate their MAO inhibitory properties. Four flavonoids from Ef leaf extract, namely, myricitrin, mearnsitrin, myricetin, and mearnsetin, are taken into consideration. Spectrofluorimetric assay is carried out to determine the MAO inhibitory properties. Next, in vitro and in vivo toxicity studies are performed in neuronal cell line and Drosophila, respectively. Furthermore, MAO inhibition by the selected compounds and their effect on dopamine levels are examined in the mouse brain. We evaluated the therapeutic potential in a mouse model of Parkinson's disease (PD) in terms of behavior, neurotransmitter levels, and dopaminergic neuronal loss. In an in vitro setup, all four compounds inhibited total MAO, whereas myricitrin exhibited some selectivity against MAO-B at 100 ?M. Myricitrin and mearnsitrin exhibited no toxicity, in vitro or in vivo. However, only myricitrin inhibited MAO in the mouse brain and elevated dopamine levels. Myricitrin was able to attenuate motor incoordination in the mouse model of PD and improved dopamine levels in the striatum.